A humoral diagnostic test outperforms cellular tests in a farm with a latent tuberculosis outbreak caused by a new Mycobacterium tuberculosis complex spoligotype that affected sheep but not goats - Juste, Ramon A.; Fernández-Veiga, Leire; Fuertes, Miguel; Fernández-Ortiz de Murua, Ignacio; Cardona, Guillermo; Geijo, Maria V.; Garrido, Joseba M.; Sevilla, Iker A. (Frontiers in Veterinary Science, 2024)
A new M. caprae spoligotype (SB2737) has been isolated from an outbreak of sheep tuberculosis affecting a mixed sheep (323)-goat (29) farm in 2021. Goats had always tested negative in annual intradermal follow-up since 2013. The index case was detected by the La Rioja slaughterhouse veterinary inspection. After tracing back to the farm of origin, only 1.2% of sheep and no goat were positive in the Comparative Intradermal Tuberculin Test, and 11.4% in a sheep subsample tested by IFN-γ release assay (IGRA) while up to 36.8% were positive in the two M. bovis-specific antibody ELISA tests. Upon confirmation of the immunologically positive sheep at slaughter by pathology and isolation, all the remaining negative animals were killed and 29.2% of sheep were still found infected. This raised the final overall prevalence to 37.5%. Antibody ELISA was the most sensitive (81.4%) in vivo detection method still showing a 85.0% specificity relative to pathological and microbiological tuberculosis status. It was nearly 10 times more sensitive than skin test and had an 86.8% positive predictive value. Notwithstanding a possible singular pathogenesis of the new spoligotype, this outbreak adds up to previous reports suggesting that sheep tuberculosis could be huge reservoir of infection worldwide overlooked by skin test low sensitivity or simply lack of investigation. This makes urgent to extend the use antibody tests to address the Trojan horse of hidden M. tuberculosis complex infections on bovine TB control programs.